Improvement of asphalt pavements during construction and repair, taking into account foreign experience. - Khabibullayev Alimardon Khidoyatillayevich; Yusupjonov Mukhriddinjon Odiljon ogli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
It is about analyzing the construction of asphalt pavements, studying foreign experience and making proposals for the introduction of foreign technologies in Uzbekistan.